I and 他 (I and him) - Wong, Karen Xue Qi (2014)
“I and 他” (I and Him) is a 20 minute narrative short film produced by twenty+ Production, a team of final year undergraduates consisting of Karen Wong, Teh Kah Soon and Yu Minli. The short film is a drama comedy, chronicling the clashes between two people from two different cultures; a Singaporean tour guide, Judy, and a tourist from Mainland China, Robert; as they set out on a journey around Singapore to find that special minced meat noodles. With a distinctively local flavour, the short film aims to deliver some laughters and at the same time, pose a social commentary on Singapore, by revealing some of Singaporeans’ idiosyncrasies and attitudes towards foreigners.